2021
DOI: 10.22541/au.162454818.82806593/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Community context modifies response of host-parasitoid interactions to phenological mismatch under warming

Abstract: Climate change is altering the relative timing of species interactions by shifting when species appear in a community and by accelerating developmental rates. However, phenological shifts may be mediated through community contexts, such as intraspecific competition and alternative resource species, which can prolong the otherwise shortened windows of availability. Using a combination of laboratory experiments and dynamic simulations, we quantified how the effects of phenological shifts in Drosophila-parasitoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…However, increasing predator diversity should be generally beneficial for top-down control by increasing the chances to have a more effective natural enemy species in the community, as it was the case in our study (i.e., sampling effect model [64]). Moreover, presence of multiple species in the community could buffer any mismatch between predator and prey species induced by warming [65]. Ganaspis sp .…”
Section: Discussionmentioning
confidence: 99%
“…However, increasing predator diversity should be generally beneficial for top-down control by increasing the chances to have a more effective natural enemy species in the community, as it was the case in our study (i.e., sampling effect model [64]). Moreover, presence of multiple species in the community could buffer any mismatch between predator and prey species induced by warming [65]. Ganaspis sp .…”
Section: Discussionmentioning
confidence: 99%
“…A very high mortality rate of the immature stages of Aganaspis daci (Weld) (Hymenoptera: Figitidae), a natural enemy of Ceratitis capitata (Wiedemann) (Diptera: Tephritidae), was observed at 15 and 30 • C [182]. Qiu et al [183] reported that at 26 • C Microplitis manilae (Ashmead) (Hymenoptera: Braconidae) presented maximum parasitism rate on Spodoptera exigua (Hübner) and Spodoptera litura (Fabricius) (Lepidoptera: Noctuidae), which significantly dropped at 32 • C. Similarly, other laboratory experiments have demonstrated a reduced parasitism rate, short lifespan, and high pupal mortality when temperature exceeded the thermal limit of the parasitoids [64,179,[184][185][186].…”
Section: Temperature Tolerance Ranges and Implications For Biocontrol...mentioning
confidence: 90%
“…sampling effect model [64]). Moreover, the presence of multiple species in the community could buffer any mismatch between predator and prey species induced by warming [65]. Ganaspis sp.…”
Section: (D) Similar Effects Of Intra-versus Interspecific Multiple P...mentioning
confidence: 99%